Development and change of the concept of hybrid war - Richard Stojar (Vojenské rozhledy, 2017)
The aim of the paper is description and analysis of the transformation of the concept of hybrid war. The Russian intervention in Ukraine in 2014 meant principal re-definition of the concept which is reflected in the contemporary views on the hybrid wars and hybrid threats. The concept of hybrid war had been questioned in the past already as his validity and the efforts to be applied on the past conflicts deformed its innovative content. One could argue, that adding new dimensions and topic such as economic factors, ideological activity etc. brings risk of concept´s expansion which goes far behind of the framework of the phenomenon of the war and the use of armed forces in the armed conflicts. The author draws attention to the fact that the definition of hybrid war tends to be subordinate to the current needs, which in turn only hinders their explanation potential.